2016
DOI: 10.1097/bpb.0000000000000245
|View full text |Cite
|
Sign up to set email alerts
|

The normal and fractured physis: an anatomic and physiologic overview

Abstract: The growth plate (physis) is responsible for enabling and regulating longitudinal growth of upper and lower limbs. This regulation occurs through interaction of the cells in the growth plate with systemic and locally produced factors. This complex interaction leads to precisely controlled changes in chondrocyte size, receptors, and matrix, which ultimately result in endochondral bone formation. With advances in cellular and molecular biology, our knowledge about these complex interactions has increased signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Related to these examples of structural and genetic studies of physes, various animal models have been coincidentally established to study growth plates in their healthy and diseased states. In this regard, different animal models have shown similarity to human models in demonstrating altered microscopic architecture under mechanical compression ( Hosseinzadeh and Milbrandt, 2016 ; Alberty et al, 1993 ; Stokes et al, 2007 ; Rudicel et al, 1985 ; Amini et al, 2010 ). More recently, Bries et al ( Bries et al, 2012 ) reported that, as in human physes ( Scharschmidt et al, 2009 ), there was decreased gene expression of aggrecan, type II and type X collagen in rabbit physes subjected to compression.…”
Section: Introductionmentioning
confidence: 99%
“…Related to these examples of structural and genetic studies of physes, various animal models have been coincidentally established to study growth plates in their healthy and diseased states. In this regard, different animal models have shown similarity to human models in demonstrating altered microscopic architecture under mechanical compression ( Hosseinzadeh and Milbrandt, 2016 ; Alberty et al, 1993 ; Stokes et al, 2007 ; Rudicel et al, 1985 ; Amini et al, 2010 ). More recently, Bries et al ( Bries et al, 2012 ) reported that, as in human physes ( Scharschmidt et al, 2009 ), there was decreased gene expression of aggrecan, type II and type X collagen in rabbit physes subjected to compression.…”
Section: Introductionmentioning
confidence: 99%
“…The metaphyseal portion of long bones is typically the primary site for the seeding of hematogenous musculoskeletal infections [ 9 – 12 ]. The physis, which is located within the metaphyseal portion, is the center at which endochondral ossification occurs to promote long bone growth in the developing skeleton [ 13 ]. This region of the bone is highly vascular due to the high cellular metabolic activity required for new bone formation [ 14 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trauma to long bones can result in the formation of a “bony bar,” which can span the physis, halt bone growth, and cause limb length discrepancies and/or angular deformities 2–5 . The current treatment to prevent these deformities includes surgical resection of the bony bar, followed by insertion of an inert interpositional material, such as silicone to prevent bony bar reformation 6,7 . However, these treatments are largely unsuccessful as the bony bar commonly recurs and negatively affects bone growth 8–10 .…”
Section: Introductionmentioning
confidence: 99%